2001
DOI: 10.1046/j.1365-294x.2001.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘rare allele phenomenon’ in a ribosomal spacer

Abstract: We describe the increased frequency of a particular length variant of the internal transcribed spacer 1 (ITS-1) of the ribosomal DNA in a hybrid zone of the land snail Albinaria hippolyti. The phenomenon that normally rare alleles or other markers can increase in frequency in the centre of hybrid zones is not new. Under the term 'hybrizyme' or 'rare allele' phenomenon it has been recorded in many organisms and different genetic markers. However, this is the first time that it has been found in a multicopy locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…This rare hybrid‐zone allele also showed up in our 2004 samples of P. appalachiensis (Table 3). Hybrizymes are rare alleles that occur only in hybrid zones, presumably as a result of: (1) increased mutation rates, (2) positive selection on the allozyme itself, or (3) ‘purifying selection’ against especially unfit multilocus hybrid genotypes which are continually purged from hybrid populations, resulting in the rare allele increasing in frequency where the selection takes place (Woodruff, 1989; Schilthuizen et al., 2001, 2004; Seehausen, 2004a,b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This rare hybrid‐zone allele also showed up in our 2004 samples of P. appalachiensis (Table 3). Hybrizymes are rare alleles that occur only in hybrid zones, presumably as a result of: (1) increased mutation rates, (2) positive selection on the allozyme itself, or (3) ‘purifying selection’ against especially unfit multilocus hybrid genotypes which are continually purged from hybrid populations, resulting in the rare allele increasing in frequency where the selection takes place (Woodruff, 1989; Schilthuizen et al., 2001, 2004; Seehausen, 2004a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Recent detection and the high frequencies of the hybrizyme Ldh‐20 in the ‘false second’ flight of the hybrid swarm of the Battenkill River Valley, and its detection in P. appalachiensis , will be examined in relation to potential functional roles in delayed post‐diapause adult eclosion and relationships with other X‐linked recombinants. Hybrizymes, which may be single base pair substitutions (Bradley et al., 1993; Johns & Somero, 2004), are assumed likely to be transient in nature due to recombination eventually breaking up the linkages (Barton & Hewitt, 1985; Hoffman & Brown, 1995; Schilthuizen et al., 2001). However, the fixation of hybrizymes in conjunction with recombinant hybrid speciation may persist as novel genotypes (Arnold, 1997; Coyne & Orr, 2004; Schilthuizen et al., 2001 and 2004; Seehausen, 2004a,b), as we suspect to be the recent case in our Papilio hybrid zone (Scriber et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The 'rare allele phenomenon', i.e., the high frequency of new or otherwise seldom alleles is a surprisingly common feature in classical hybrid zones (review in Barton & Hewitt, 1985;Woodruff, 1989;Collins, Britten & Rivers, 1993;Keenan, 1994;Krutovskii & Bergmann, 1995;Schilthuizen, 1995;Guiller, Coutellec-Vreto & Madec, 1996;Schilthuizen, Hoekstra & Gittenberger, 2001) but has hardly been reported in contact-populations with random mating. Barton & Hewitt (1985) reviewed studies from 23 hybrid zones; 19 studies observed the rare allele phenomenon but only one study reported random mating (i.e.…”
Section: The Rare Allele Phenomenonmentioning
confidence: 99%
“…Schilthuizen, Hoekstra & Gittenberger, (2001) stressed the importance of natural selection, either on the gene itself or on loci linked with it. Selection leads to higher frequencies of those markers that are in linkage disequilibrium with the selected loci.…”
Section: The Rare Allele Phenomenonmentioning
confidence: 99%
“…Genetic chimera explain not only the sustention of genetic diversity of horticultural C. taitungensis but also the distinction between cultivated and wild samples of C. revoluta (Table 1), which is broadly evidenced in microbes [25,26]. Hybridizing recombination would also raise the number of rare alleles [27,28] especially in those newly derived hybrids [29]. However, this speculation of genetic chimera is difficult to test by AFLP markers and we hope to test this further by codominant-marker surveys (e.g., by microsatellite DNAs) like the beautiful case of grapevine [30,31].…”
Section: Discussionmentioning
confidence: 99%